Exclusive Breast Feeding in a Bangladesh National Nutrition Program Area: The Case in Bhanga Upazila - Karim, Rezaul; Khan, Md Nazrul Islam; Akhtaruzzaman, Md (Bangladesh Journal of Nutrition, 2015)
A statistically selected representative sample of 482 households in Bhanga upazila was studied to observe mother's knowledge and practice of the right duration of exclusive breast-feeding in an NNP area. Although a large number of mothers knew the right duration of exclusive breast-feeding, fewer practiced it for their last infant. Apart from some health constratints, lack of knowledge and motivation were the main reasons for early and late introduction of supplementary feeding. Regular participation in GMP sessions improved mother's knowledge of the right duration of exclusive breast-feeding, and improved knowledge increased practice while higher levels of mother's literacy accelerated the learning. Literate mothers were three times more likely and mothers who participated in GMP sessions regularly were almost three times more likely to know the right duration of exclusive breast-feeding compared to illiterate mothers and mothers who never participated in GMP sessions respectively. Mothers who knew the right duration were about 28 times more likely to practice it compared to the mothers who did not know it. A strong public awareness campaign aimed at the mothers could better motivate them to participate in GMP sessions more regularly leading to improved knowledge and increased practice of the right duration of exclusive breast-feeding realizing the full potential of NNP.